Learning Microsoft Word 2013 - Guy Vaccoro; Safari eBooks ([S.l] : Infinite Skills, 2013)
"In this Microsoft Word 2013 training course, expert trainer Guy Vaccaro teaches you how to use this popular word processing software. You will learn the basics of creating and formatting documents in Word, and how to use the most popular tools that Microsoft makes available to you in the 2013 release. This tutorial is designed for the absolute beginner and no prior experience in Microsoft Word is required. In this Microsoft Word 2013 training course, expert trainer Guy Vaccaro teaches you how to use this popular word processing software. You will learn the basics of creating and formatting documents in Word, and how to use the most popular tools that Microsoft makes available to you in the 2013 release. This tutorial is designed for the absolute beginner and no prior experience in Microsoft Word is required.Guy will show you how to create and format your Word 2013 documents in short, easy to understand videos. Using the working files that are provided, you will be able to practice the lessons throughout this Word 2013 tutorial, re-enforcing what you learn. Some of the topics that are covered include; setting document properties, adding headers and footers, protecting your documents, formatting your text, working with tables, using Autotext and creating a Mail Merge. You will also learn how to add shapes, images and even charts to your documents. Finally, Guy will show you how to publish your document to the web and even how to edit it online! Once you have completed this Microsoft Word 2013 video training course, you will be familiar with the features most used on a day to day bases. You will be capable creating and formatting both simple and complex Word documents either for personal use, or in a professional environment."--Resource description page.
Title from resource description page (viewed Aug. 8, 2013).
Presenter, Guy Vaccaro.
Keywords: Microsoft Word; Word processing; Electronic books